A PECULIARITIES OF DETECTIVE GENRE IN ENGLISH AND UZBEK LITERATURE: PECULIARITIES OF DETECTIVE GENRE IN ENGLISH AND UZBEK LITERATURE - Shodiyarova, Mohira (Журнал иностранных языков и лингвистики, 2022)
The article analyzes the works of the detective genre English and Uzbek literature. The rich traditions of the detective genre in English literature are noted, the works of A. Christie stand out in particular, and it is indicated that this genre is taking its first steps in Uzbek literature.